Advancing Tourism and Creative Economy in DKI Jakarta: Strategic Policy Initiatives Based on Global Benchmarking and Qualitative-Conceptual Analysis - Astuti, Marhanani Tri; Putranto, Diyan; Mialwati, Milawati (Commercium : Journal of Business and Management, 2025)
This study examines strategic policy initiatives to advance tourism and the creative economy in DKI Jakarta by integrating global best practices with Jakarta’s unique urban dynamics. Employing a qualitative-conceptual approach and global benchmarking, the research identifies how leading cities have successfully balanced visitor growth, creative sector development, and sustainability, and adapts these lessons to Jakarta’s context. The findings reveal Jakarta’s creative economy is vibrant and economically significant, yet its growth is hindered by uneven benefit distribution, fragmented governance, and infrastructure constraints. The article’s novelty lies in its context-sensitive framework that tailors international strategies—such as green infrastructure, digital innovation, and inclusive creative hubs—to Jakarta’s socio-economic and institutional realities, offering actionable pathways rarely addressed in existing literature. Key recommendations for policymakers include: (1) prioritizing sustainability through climate-adaptive infrastructure and environmental monitoring; (2) accelerating digital transformation to enhance visitor experiences and support creative entrepreneurs; and (3) fostering inclusive governance that equitably distributes tourism and creative economy benefits, especially to local communities. These focused policy directions are designed to boost Jakarta’s global competitiveness, resilience, and inclusivity in the tourism and creative sectors.